Modelo animal no estudo de porfirias: perfil de alterações neuropsiquiátricas e disautonômicas - Barros, Rodrigo Fernandes de (2016)
Porphyrias are clinical conditions arising from congenital or acquired enzyme deficiencies in the biochemical pathway of heme. Acute intermittent porphyria (AIP) is one of the main forms of congenital hepatoporphyria, which affects individuals causing liver and autonomic nerve dysfunctions, and neuropsychiatric symptoms, leading to neuropathic pain and hemodynamic instability as well as hallucinations and social behavior problems. Many of these pathological effects on AIP occur due to accumulation of 5-aminolevulinic acid (ALA), an early residue in the biosynthesis of heme. Using two rodent models of AIP, our goal was to search for and characterize changes in social behavior in parallel to determine the disarrangements in hemodynamic response and pain threshold described in patients with acute AIP symptoms. For the behavioral and pain studies, we used the mouse strain C57BL/6 with both males and females. Male and female Wistar rats were used on experimental trials for accessing the hemodynamic parameters. At the end of the treatment, where animals were chronically exposed to high concentrations of ALA (40 mg/ml), we sequentially tested behavioral paradigms of motor locomotion, exploratory behavior and anxiety level (open field and marble burying paradigms), neuropathic pain (Von Frey’s electronic method) and offensive aggressiveness (resident-intruder paradigm). The hemodynamic parameters were assessed both non-invasively with ultrasound/color Doppler and invasively with direct recordings blood pressure, heart rate and cardiovascular autonomic modulation by spectral analysis. Behavioral paradigms showed that long-term treatment with ALA promoted an important reduction in motor locomotion in both males and females and very low propensity for offensive aggression in males relative to controls. In addition, there was marked increase in the perception of pain of neurogenic condition. Our method with ultrasound/Doppler allowed the investigation of the mesentericportal venous system, which presented lower blood flow in ALA-treated subjects than male and female measures in animal controls. Although we did not notice any changes in the main cardiovascular parameters (e.g.; blood pressure and heart rate), spectral analysis of heart rate variability and systolic blood pressure in time and frequency domains showed altered autonomic sympathetic and parasympathetic controls. Altogether, our findings reveal the effects of long-term exposure of ALA as an important mechanism for central and peripheral nervous system disarrangements in porphyria-like conditions. They also may advance not only diagnostic tools and methods to access porphyrias and heme disorders-related clinical signs and symptoms but also the medical and rehabilitation care of the neuropsychiatric aspects and cardiovascular dysautonomia of affected individuals.